Desymmetrized hexasubstituted [3]radialene anions as aqueous organic catholytes for redox flow batteries. Issue 18 (5th February 2020) - Turner, Nicholas A.; Freeman, Matthew B.; Pratt, Harry D.; Crockett, Austin E.; Jones, Daniel S.; Anstey, Mitchell R.; Anderson, Travis M.; Bejger, Christopher M.
Abstract : Hexasubstituted [3]radialenes can be synthetically tuned to function as catholyte materials for neutral pH aqueous organic redox flow batteries. Abstract : Negatively substituted trimethylenecyclopropane dianions, a subclass of hexasubstituted [3]radialenes, are candidates for use as active species in redox flow batteries (RFBs) due to their stability in water, reversible electrochemistry, and tailorable synthesis. Hexacyano[3]radialene disodium is investigated as a pH 7 aqueous organic catholyte. The dianion and radical anion are stable in air and aqueous solutions at neutral pH. Systematic introduction of asymmetry via step-wise synthesis leads to enhanced solubility and higher capacity retention during galvanostatic cycling. An aqueous flow cell comprising a diester-tetracyano[3]radialene catholyte, sulfonated-methyl viologen as the anolyte, and a cation exchange membrane provides an operating V cell = 0.9 V, 99.609% coulombic efficiency, and minimum capacity fade over 50 cycles.